Sound souvenirs: audio technologies, memory and cultural practices - Bijsterveld, K; Van Dijck, J (Transformations in Art and Culture, 2009)
In recent decades, the importance of sound for remembering the past and for creating a sense of belonging has been increasingly acknowledged. We keep "sound souvenirs" such as cassette tapes and long play albums in our attics because we want to be able to recreate the music and everyday sounds we once cherished. Artists and ordinary listeners deploy the newest digital audio technologies to recycle past sounds into present tunes. Sound and memory are inextricably intertwined, not just through the commercially exploited nostalgia on oldies radio stations, but through the exchange of valued songs by means of pristine recordings and cultural practices such as collecting, archiving and listing. This book explores several types of cultural practices involving the remembrance and restoration of past sounds. At the same time, it theorizes the cultural meaning of collecting, recycling, reciting, and remembering sound and music. Herinneringen halen we niet alleen op aan de hand van beelden, maar ook met behulp van geluid. We koesteren onze versleten bandrecorderspoelen, cassettebandjes en langspeelplaten - onze "sound souvenirs" - om de muziek van vroeger nog eens te horen. Radioprogramma's als de Top2000 houden oude nummers eindeloos in de lucht. In geluidsarchieven bewaren we de redes van beroemde politici. In de auto nemen we voortdurend onze persoonlijke muziekbestanden met ons mee. En een enkele keer worden we herinnerd aan geluiden die we liever vergeten, zoals die van bombardementen. Dit boek verkent de verschillende culturele praktijken waarin we het geluid van het verleden gewenst en ongewenst terughalen en probeert de culturele betekenis van het verzamelen, citeren en herinneren van geluid en muziek te begrijpen. Met bijdragen van Ruth Benschop, Carolyn Birdsall, Hans-Joachim Braun, Michael Bull, Karin Bijsterveld & Annelies Jacobs, José van Dijck, Andreas Fickers, Bas Jansen, Trevor Pinch & David Reinecke, Jonathan Sterne, Tim Taylor en Heike Weber.